Bronze Stamps from Antioch-on-the-Orontes and Rest of Turkey Antiochiae haereditati latinae, terrae motu destructae anno MMXXIII - Laflı, Ergün 1975-; Buora, Maurizio 1947- (2025)
In this brief article we present a collection of eleven bronze bread stamps of the Early Byzantine period which are preserved in the Archaeological Museum of Hatay, i.e., ancient Antioch-on-the-Orontes in south-eastern Turkey that played a fundamental role in the shaping and developing of political life and cultures in the Greek, Roman and Byzantine East for more than a millennium. Eleven items are catalogued here in detail and identified as Late Antique-Early Byzantine bread stamps with, for the most part, Christian symbolism or connotations.
At appendix 1 at the end of the paper seven Roman and Early Byzantine bronze and terracotta stamps from Turkish museums in eastern central Turkey and at appendix 2 two Early Byzantine bronze objects with monograms from the Archaeological Museum of Izmir are treated.
Keywords: museum studies; Early Christian Near East; Byzantine archaeology; Byzantine epigraphy; Syria; Turkey; Antioch-on-the-Orontes; instrumenta inscripta; bronze bread stamps / signacula